O bloqueio dos receptores glicocorticóides da região infralímbica do córtex pré-frontal medial facilita a aquisição, mas não a consolidação da memória de camundongos submetidos ao protocolo de teste e reteste no labirinto em cruz elevado - Fonseca, Aura Julieth Rodriguez (2018)
A single experience (test) in the elevated plus maze (EPM) increases the avoidance of open arms and impairs the anxiolytic efficacy of the midazolam benzodiazepine agonist (MDZ) in a subsequent re-esposition (retest). Phenomenon known in the literature as "one trial tolerance" (OTT). Studies consider that OTT is due to a memory of the first exposure that allows changes in the strategy adopted at retest or day 2. Glucocorticoid receptors in the infralimbic subregion (IL) of the medial prefrontal cortex (mPFC) have been described as important modulators of learning and cognition; however, their involvement in establishing OTT remains unknown. This study investigated the effects of bilateral injection intra- mPFC -IL of RU486 (glucocorticoid receptor antagonist, GR) in the acquisition and consolidation phases of the memory of mice submitted to the test and retest protocol on the EPM. Experiment 1 (acquisition phase): independent groups of Swiss male mice received either intra-IL bilateral vehicle injection or RU486 (0.3 or 1 ng / 0.1μL) 5 minutes before the test and were exposed to EPM for 5 minutes. Twenty-four hours later, the subjects received vehicle injections or MDZ (2 mg/kg) (i.p), 30 minutes before retest in the EPM. Experiment 2 (consolidation phase): similar to Experiment 1, except that the animals in each group were exposed to the EPM test for 5 minutes, and after received injection intra- mPFC -IL of vehicle or RU486. The analysis of variance (ANOVA) followed by Duncan's post hoc showed that in Experiment 1, prior to the test period, none of the doses of RU486 had an effect on OTT for MDZ, suggesting no effect on the phase of memory acquisition. However, the combined treatment was able to reduce behavioral parameters such as risk assessment (SAP) in the reexposure to EPM. For Experiment 2 after the test period, none of the doses of RU28318 had an effect on OTT for MDZ, suggesting no effect on the memory consolidation phase. These results indicate that RU486 does not play a role on the memory acquisition of a trial 1 in the EPM, however was observed attenuation on anxiety-like behaviors. Additionally, our data indicate that RU486 does not play a role on the memory consolidation of a trial 1 in the EPM. Taken together, the present results demonstrate that the glucocorticoid receptors located within the mPFC -IL are involved in the development of mnemonic aspects related to learning in aversive situations.